THE STUDY OF FEARS AND ANXIETY IN CHILDREN - Kazaxbaeva Mexriban Jamalatdin qizi; Sadikova Qizjibek Quralbay qizi; Dùysenbaeva Bibigùl Bekmurzaevna; Najimatdinova Gulnaz Muyatdinovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: This article studies fear in children.